PENYULUHAN HUKUM KEAMANAN MEDIA SOSIAL BAGI IBU-IBU PKK DI RT 10 RW 12 PERUMAHAN THE PALM KEC TAMBUN UTARA - Clara Ignatia Tobing; Jantarda Mauli Hutagalung (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Social media is often used to convey negative things.Hoaxes, and hate speech appear non-stop on social media. Onegroup of people heavily involved in the spread of fake news arehousewives. This is due to ignorance which leads to criminalacts which housewives also do not know about theconsequences of spreading false information through socialmedia. To prevent this, counseling was held for the PKK groupRT 10 RW 12 The Palm Housing which is located in the NorthTambun area, Bekasi. This service activity offers solutions inthe form of seminars and education of concepts and rulesrelated to social media security, with the output of increasingparticipants' understanding regarding the identification, useand prevention of the hoaxes..